Developing system thinking skills through project-based learning loaded with education for sustainable development - Ria Anita Ekselsa; Widi Purwianingsih; Sri Anggraeni; Azizul Ghofar Candra Wicaksono (University of Muhammadiyah Malang, 2023)
High school students need to be introduced to and trained in system thinking skills as one of the implementations of Education for Sustainable Development (ESD). This study aimed to develop high school students' systems thinking skills through ESD-laden project-based learning on environmental change material. A pre-experimental method was applied with the One Group Pretest Posttest Design to 35 class X high school students in Bandung Regency who were selected by non-random sampling. The data were collected through open questions to evaluate students' systems thinking skills and were processed by scoring student answers based on the rubric for assessing system thinking skills. The N-Gain value was calculated to determine the magnitude of the increase in students' systems thinking skills before and after learning. The results showed that the N-Gain value was 0.64, which means that students' systems thinking skills moderately developed after project-based learning containing ESD. The development of system thinking skills can train students to change paradigms to view a problem from various perspectives to find a sustainable solution, encouraging them to pay more attention to their activities and take more responsible actions.